Cruise passenger satisfaction and the role of past experience: Analysis of user-generated content - Medina, Ana Rita Ribeiro Costa (2024)
This study examines cruise passengers’ satisfaction based on user-generated content (i.e.,quantitative ratings and narratives shared online). 416 text reviews and the corresponding ratings of eight quality attributes - ‘Entertainment’, ‘Dining’, ‘Fitness and Recreation’, ‘Cabins’, ‘Public Rooms’, ‘Value for Money’, ‘Embarkation’, and ‘Service’ - were collected from the Cruise Critic website for the cruise company with the highest market value and largest fleet worldwide, Royal Caribbean International, for which 16 reviews were collected for each one of the company’s 26 ships. The relationships between cruisers’ Overall Satisfaction and each quality attribute, grounded in literature, were tested and proved to positively affect Overall Satisfaction, having ‘Value for Money’ stood out with the strongest impact. Past Cruising Experience was proved to negatively affect guests’ Overall Satisfaction, meaning that the higher the level of cruising experience, the lower the Overall Satisfaction tends to be, reflecting the high standards and expectations of the most experienced cruisers. Moderated Linear Regressions were used to analyse the moderating role of Past Experience on the relationships between each quality attribute and Overall Satisfaction. The moderating effects were found significant when regarding satisfaction with ‘Cabins’, ‘Public Rooms’, the ‘Embarkation’ process, and the ‘Service’ quality. The latter relationship was found to be the most sensitive to the moderating role of Past Experience. In general, the moderator tended to strengthen the direct relationship between the predictor and the Overall Satisfaction, as the level of experience decreased, proving that least experienced cruisers are more sensitive to improvements in these quality attributes.